2021
DOI: 10.1186/s12916-021-02053-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Norfolk diabetes prevention lifestyle intervention (NDPS) on glycaemic control in screen-detected type 2 diabetes: a randomised controlled trial

Abstract: Background The purpose of this trial was to test if the Norfolk Diabetes Prevention Study (NDPS) lifestyle intervention, recently shown to reduce the incidence of type 2 diabetes in high-risk groups, also improved glycaemic control in people with newly diagnosed screen-detected type 2 diabetes. Methods We screened 12,778 participants at high risk of type 2 diabetes using a fasting plasma glucose and glycosylated haemoglobin (HbA1c). People with scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 73 publications
(104 reference statements)
0
3
0
Order By: Relevance
“…Lifestyle interventions including a healthy diet accompanied by a significant increase in physical activity can prevent the risk of T2DM by 40% - 47% for 2 years [ 29 ]. Furthermore, the cost of T2DM cases prevented from various study analysis demonstrated that lifestyle intervention resulting in an equivalent reduction in health care costs [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lifestyle interventions including a healthy diet accompanied by a significant increase in physical activity can prevent the risk of T2DM by 40% - 47% for 2 years [ 29 ]. Furthermore, the cost of T2DM cases prevented from various study analysis demonstrated that lifestyle intervention resulting in an equivalent reduction in health care costs [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Previous studies found that younger participants with diabetes often have better therapeutic effects than older adults and dietitian-led interventions can achieve greater weight reduction. 30,31 The American Diabetes Association also recommends that a multidisciplinary team promoting diabetes education should include at least one registered dietitian. 32 However, primary health care members in China are unevenly distributed across the country, especially in Western regions where our research was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Sampson and colleagues implemented an IP diet and lifestyle intervention with and without additional telephone support provided by trained peers in the UK for individuals with newly diagnosed "screen detected" type 2 diabetes [27]. Participants were randomized into three arms.…”
Section: Ip Diet and Lifestyle Intervention With Telephone Supportmentioning
confidence: 99%